When a Plant Resistance Inducer Leaves the Lab for the Field: Integrating ASM into Routine Apple Protection Practices - Marolleau, Brice; Gaucher, Matthieu; Heintz, Christelle; Degrave, Alexandre; Warneys, Romain; Orain, Gilles; Lemarquand, Arnaud; Brisset, Marie-Noëlle (Frontiers in Plant Science, 2017)
Abstract Plant resistance inducers, also called elicitors, could be useful to reduce the use of pesticides. However their performance in controlling diseases in the field remains unsatisfactory due to lack of specific knowledge of how they can integrate crop protection practices. In this work, we focused on apple crop and acibenzolar-S-methyl (ASM), a well-known SAR (systemic acquired resistance) inducer of numerous plant species. We provide a protocol for orchard-effective control of apple scab due to the ascomycete fungus Venturia inaequalis, by applying ASM in combination with a light integrated pest management program. Besides we pave the way for future optimization levers by demonstrating in controlled conditions i) the high influence of apple genotypes, ii) the ability of ASM to prime defenses in newly formed leaves, iii) the positive effect of repeated elicitor applications, iv) the additive effect of a thinning fruit agent.